Effects of match period and playing position on the individual and collective dynamics in professional soccer: a case study - Praça, G. M.; de Andrade, A. G.; da Glória Teles Bredt, S.; Drumond Moreira, P. E.; De Conti Teixeira Costa, G.; de Oliveira Castro, H.; Aquino, R. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2020)
This study aimed to compare the width, the length, the length per width ratio, and the stretch index between the first and the second halves in official soccer matches, and to compare the spatial exploration index between players from different positions. Seventeen professional soccer players from a Brazilian club participated in the study and were monitored during six official matches by a GPS device. Collective positional data were compared between the two halves using a paired t-test, while the spatial exploration index was compared between the playing positions and within the halves by a mixed two-way ANOVA. The results revealed no differences between the two halves for the collective variables. The highest values of spatial exploration index were reported for central midfielders and wing forwards. We conclude that the tactical behavior of professional soccer players is position-dependent, and midfielders are the most exploratory players on the pitch.